PEMBERDAYAAN IBU TERKAIT STIMULASI TUMBUH KEMBANG ANAK MELALUI PENDEKATAN MODELING - Chairy, Abdul; Jumhati, Siti (Universitas Mohammad Husni Thamrin, 2021)
ABSTRACTBackground : Pregnancy is a very meaningful experience for women. Examination and supervision of pregnant women really needs to be carried out regularly. This aims to prepare the mother and child as optimally as possible physically and mentally during pregnancy, childbirth and postpartum so that a healthy mother and child are obtained. For pregnant women who have never been pregnant or given birth before (primigravida), pregnancy or childbirth is something foreign to them. This is because it is something new he has experienced. Family support, especially husbands, greatly influences antenatal care (ANC) visits for primigravida mothers. Family support is able to motivate primigravida mothers to visit antenatal care. Antenatal care is a pregnancy examination carried out on pregnant women during their pregnancy to prevent complications during pregnancy and to prepare for a healthy birth.Objective : This study aims to determine whether there is a relationship between husband and family empowerment and compliance with antenatal care (ANC) for pregnant women in the Pasar Rebo Health Center working area.Methods: This research used an analytical research design with a cross sectional approach which was carried out at the Air Salobar Community Health Center with a sample size of Â 32 respondents. Data collection was carried out using questionnaires and observation sheets. From the Chi Square statistical test.Results: The results of this study indicate that there is a significant relationship between husband's support and compliance with ANC visits (p = 0.003).Conclusions and suggestions: The conclusion of this research is that there is a significant relationship between family support and compliance with ANC visits for pregnant women at the Pasar Rebo Health Center. This research is expected to provide information and understanding to pregnant women, husbands and community health center midwives about the relationship between family support and compliance with antenatal care (ANC) in pregnant women.Recommendation: In further research, it is hoped that research can be developed even betterÂ Keywords: Â Family Support, Compliance in Antenatal Care Visit